1994
DOI: 10.2136/sssaj1994.03615995005800050034x
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and Water Flow Patterns in Every‐Furrow and Alternate‐Furrow Irrigation

Abstract: Deep water percolation and chemical leaching is a recognized environmental problem with furrow irrigation. Alternate‐furrow irrigation (AFI) was hypothesized as a method to increase water‐use efficiency and decrease chemical leaching compared with every‐furrow irrigation (EFI). The SWMS_2D finite‐element model was used to investigate water and CaCl2 movement in EFI and AFI with furrow‐placed or ridge‐placed fertilizer bands. Model simulations were conducted for a Crook loamy sand (mixed, mesic, Ustic Torripsam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…1). The sidedressed N was placed nearer the plant row than furrow so that the N would be more available to the corn (Hefner and Tracy, 1995) and less susceptible to leaching if that furrow was irrigated (Benjamin et al, 1994;Saffigna et al, 1976). In both years, the border plots were sidedressed with 90 kg N ha-1 .…”
Section: Methodsmentioning
confidence: 99%
“…1). The sidedressed N was placed nearer the plant row than furrow so that the N would be more available to the corn (Hefner and Tracy, 1995) and less susceptible to leaching if that furrow was irrigated (Benjamin et al, 1994;Saffigna et al, 1976). In both years, the border plots were sidedressed with 90 kg N ha-1 .…”
Section: Methodsmentioning
confidence: 99%
“…Los métodos de riego por gravedad son los más comunes para aplicar el agua en los terrenos agrícolas de zonas áridas, semiáridas y subhúmedas a nivel mundial y en México no es la excepción (Benjamin et al, 1994;González-Camacho et al, 2006). Lo anterior es atribuible a la simpleza de su operación y al bajo consumo de energía (Cabrera, 1994).…”
Section: Introductionunclassified
“…The gravity irrigation methods are the most common to apply water on agricultural land in arid, semi-arid and sub-humid worldwide and Mexico is no exception (Benjamin et al, 1994;González-Camacho et al 2006). This is attributable to the simplicity of its operation and low power consumption (Cabrera, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The HYDRUS (2D/3D) model and its predecessors, such as SWMS-2D and HYDRUS-2D, have been widely used in the past to simulate water flow and/or solute transport for furrow irrigation systems (e.g., Benjamin et al 1994;Abbasi et al 2003aAbbasi et al , b, 2004Rocha et al 2006;Wöhling et al 2004aWöhling et al , b, 2006Mailhol et al 2007;Warrick et al 2007;Wöhling and Schmitz 2007;Wöhling and Mailhol 2007;Crevoisier et al 2008;Lazarovitch et al 2009;Ebrahimian et al 2012Ebrahimian et al , 2013aZerihun et al 2014). For example, Benjamin et al (1994) simulated fertilizer distribution in the soil under broadcast fertilization for conventional and alternate furrow irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Benjamin et al (1994) simulated fertilizer distribution in the soil under broadcast fertilization for conventional and alternate furrow irrigation. They concluded that fertilizer applied on the non-irrigated furrows may not be taken up by plants because of the low water content in the upper layer of this furrow.…”
Section: Introductionmentioning
confidence: 99%